Evaluation of the Effectiveness of a Chronic Ocular Hypertension Mouse Model Induced by Intracameral Injection of Cross-Linking Hydrogel - Chen, Junjue; Sun, Jun; Yu, Huan; Huang, Ping; Zhong, Yisheng (Frontiers in Medicine, 2021)
Objectives Glaucoma is an irreversible and blinding neurodegenerative diseases, is characterized by progressive loss of retinal ganglion cells. The current animal models of glaucoma fail to provide a chronic elevated intraocular pressure and can’t maintain the optical media clarity for a long time, which brings some difficulties to the study of glaucoma. Here, we developed a new chronic ocular hypertension model of mice induced by cross-linking hydrogel intracameral injection. Methods C57BL/6 mice aged 6-8 weeks were injected of cross-linking hydrogel to induce ocular hypertension. Intraocular press was measured preoperatively, three days after surgery and weekly until the end of the study. Flash visual evoked potential was used to observe the optic nerve function at different times after chronic ocular hypertension. The expression of retinal TNF-𝛼, IL-1𝛽 and IL-17A protein was measured by western blotting. The activation of microglial cells was evaluated by immunohistochemistry fluorescence staining and western blotting. The apoptosis and loss of retinal ganglion cells after intracameral injection of cross-linking hydrogel were observed by TUNEL assay and Brn3a protein labeling. Results Intracameral injection of the cross-linking hydrogel induces elevation of intraocular press with mean value was 19.0±0.4mmHg and sustained for at least 8 weeks, which lead to progressive loss of retinal ganglion cells. The success rate was 75%. The average amplitude of N1-P1 in mice with 2,4 weeks of chronic ocular hypertension was 6.9±3uV and 4.0±2uV, respectively. The average latent period of N1 in mice with 2,4 weeks of chronic ocular hypertension was 60.3±2ms and 66.5±2ms, respectively. The expression of TNF-𝛼, IL-1𝛽 and IL-17A protein increased in Chronic Ocular Hypertension mice. The activation of microglial cells was observed induced by Chronic Ocular Hypertension. There were statistical changes in the latent period and amplitude of eyes with intracameral injection of cross-linking hydrogel compared with the control eyes. Conclusions A single intracameral injection of cross-linking hydrogel can effectively induce chronic ocular hypertension in mice, which causes progressive loss of retinal ganglion cells, increase of expression levels of inflammatory cytokines and microglial cells activation and deterioration of optic nerve function.